Molecular cloning and the complete nucleotide sequence of the creatine kinase-M cDNA from chicken. - Kwiatkowski, R W (1984)
The nucleotide sequence of creatine kinase-M (CK-M) cDNA clones has been determined. It includes the entire coding region of 381 amino acids in addition to 5' and 3' untranslated regions. A comparison with a partial sequence from rat CK-M reveals 84% nucleotide sequence homology in the coding region but divergence in the 3' untranslated region. The amino acid sequence is 94% conserved between chicken and rat. Hybridization to RNA immobilized on filters indicates homology between the CK-M 3' untranslated region and additional muscle specific RNA species. The coding region hybridizes only to CK-M RNA.